Audiometry and doping control in competitive deaf sport - Szulc, Adam Michał; Balatoni, Ildikó; Kopeć, Sylwia (Acta Medicinae et Sociologica, 2021)
In the past forty years both the participating countries and the participants at the Summer Deaflympics Games have increased by 2.5-fold. Furthermore, there are approximately fifty European or World sports events organized for the hearing impaired. The aim of the paper was to discuss the procedures and requirements related to doping control in deaf people’s competitive sport in the context of the rising number of sports events and the participating athletes.For the sake of the fair play spirit of the dynamically developing deaf sports, The International Committee of Sports for the Deaf (ICSD) introduced rules governing the participation of hard-of-hearing athletes in sports events. Healthy individuals with a hearing loss of at least 55 dB are allowed. Thus, audiometric examination constitutes the first doping control criterion. Since 2004, ICSD has been cooperating with the World Anti-Doping Agency. The second criterion is, therefore, blood and urine sample control for prohibited substances. The 23rd Summer Deaflympics in 2017 involved 2858 athletes. Overall, 842 (29.5%) participants were randomly subjected to an audiological test; 9 competitors from different countries were disqualified because of non-compliance with the ICSD standards. A total of 300 randomly selected athletes underwent doping control for prohibited substances; 1 was disqualified. The world literature lacks scientific reports on deaf sports, including doping control.